Effect of Lactobacillus johnsonii Strain SQ0048 on the TLRs-MyD88/NF-κB Signaling Pathway in Bovine Vaginal Epithelial Cells - Cheng, Chao; Zhang, Linchong; Mu, Junxiang; Tian, Qiaozhen; Liu, Yanming; Ma, Xiaohong; Fu, Yanru; Liu, Zhiguo; Li, Zhenjun (Frontiers in Veterinary Science, 2021)
Vaginal inflammation is a common disease of the dairy cows' reproductive tract. Lactic acid bacteria can combat purulent inflammation caused by pathogenic bacteria and regulate the NF-κB signaling pathway mediated by toll-like receptors (TLRs) in the inflammatory response. We studied the effect of Lactobacillus johnsonii SQ0048, an isolate with antibacterial activity, on the NF-κB signaling pathway in cow vaginal epithelial cells. The expression levels of serial effectors related to the TLRs-MyD88/NF-κB signaling pathway (TLR2, TLR4, MyD88, IKK, NF-κB, IL-1β, IL-6, TNF-α, and IL-10) were measured with real-time polymerase chain reaction (RT-PCR), ELISA, and Western blot analyses. TLR2 and TLR4 were activated by SQ0048 cells, as noted by increased mRNA expression levels of TLR2 and TLR4 in SQ0048-treated bovine vaginal epithelial cells relative to control cells (P <0.01). SQ0048 treatment also significantly increased MyD88 and IKK expression, and activated NF-κB in vaginal epithelial cells (P <0.01). In addition, SQ0048 treatment also significantly increased mRNA expression levels of IL-1β, IL-6, and TNF-α, but decreased IL-10 mRNA expression levels (P <0.01). These data indicate that strain SQ0048 presence can improve the immune functions of cow vaginal epithelial cells by activating TLRs-MyD88/NF-κB signaling pathways. However, further in vivo studies are required to confirm these findings.